Pionierskość i aktualność przemyśleń Friedricha Georga Jüngera z „Perfekcji techniki” - Citkowska-Kimla, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim of the article is to show the inventiveness and topicality of F.G. Jünger’s considerations contained in his work entitled The Perfection of Technology. The article aims at outlining that Jünger’s attitude towards technology was evolving from delight to severe criticism. Moreover Jünger is depicted as athinker par excellence, as athinker whose thought reached the timeless dimension.
Keywords: Jünger, Friedrich Georg; perfekcja technologii; technologia; twórcze lenistwo; powolne życie; rewolucyjny konserwatyzm